2015
DOI: 10.1002/pros.23130
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological features of intra-ductal carcinoma of prostatic and high grade prostatic intraepithelialneoplasia and correlation with PTEN and P63

Abstract: We found that IDC-P had a unique histoclinical feature and was strongly associated with poor prognostic factors. Diagnosis and report of IDC-P should be considered in all prostate specimens. Also, we recommend PTEN IHC application for differentiated IDC-P from HGPIN in biopsies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…With PTEN loss in two third of the cases, the concordance between IDC-P and adjacent carcinoma was 81% [69]. PTEN loss has also been observed in almost 90% of 40 IDC-P cases compared to 0% of 40 HGPIN cases [77]. Downes et al [74] further verified the concordance of ERG and PTEN expression patterns in IDC-P, CC and the adjacent invasive carcinoma in a cohort of 57 PCa cases with cribriform morphology.…”
Section: Pten and Erg (Tmprss2:erg)mentioning
confidence: 90%
See 1 more Smart Citation
“…With PTEN loss in two third of the cases, the concordance between IDC-P and adjacent carcinoma was 81% [69]. PTEN loss has also been observed in almost 90% of 40 IDC-P cases compared to 0% of 40 HGPIN cases [77]. Downes et al [74] further verified the concordance of ERG and PTEN expression patterns in IDC-P, CC and the adjacent invasive carcinoma in a cohort of 57 PCa cases with cribriform morphology.…”
Section: Pten and Erg (Tmprss2:erg)mentioning
confidence: 90%
“…Contrary to PTEN, TM-PRSS2:ERG fusion or ERG expression has not been clearly linked to PCa outcome and is mostly used as a diagnostic marker [93][94][95][96][97]. Since the expression of ERG and PTEN can be evaluated by IHC, a very accessible histopathology technique, these two markers are the most studied in IDC-P [66][67][68][69][70][71][72][74][75][76][77][78]98].…”
Section: Pten and Erg (Tmprss2:erg)mentioning
confidence: 99%
“…Although the biological nature of IDC‐P is an enigma, recent studies have indicated that the IDC‐P component is endowed with resistance to androgen deprivation therapy (ADT) and a high invasive capacity. In addition, several studies have shown that PTEN loss is more enriched in IDC‐P components than in ordinary invasive PCa 7–14 . PTEN is a tumor suppressor and one of the most frequently genetically altered genes in advanced PCa 15 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies have shown that PTEN loss is more enriched in IDC-P components than in ordinary invasive PCa. [7][8][9][10][11][12][13][14] PTEN is a tumor suppressor and one of the most frequently genetically altered genes in advanced PCa. 15 PTEN loss has also been shown to induce resistance to ADT combined with TP53 and/or Rb alterations.…”
Section: Introductionmentioning
confidence: 99%